DOES THE TEMP-DECISION CONTRIBUTE TO THE RESTORATION OF THE EMPLOYABILITY? - Paraskeva Mancheva (Peytchinski Publishing, 2020)
Introduction: A hot topic of the discussions about the reforming of the Territory Expert Medical Commission system (TEMC) is the restoration process of peoples' health and ability to work. The expert decision, given by TEMC offers an opportunity for social adaptation for disabled people, whilst restoring their ability to work, all by using the methods and resources of rehabilitation. The aim of the article is to study and analyze the opinion of disabled people on the role of the expert's decision by TEMC to restore employability. Material and Methods: The study's sample was prepared on the basis of the register of General Territory Expert Medical Commission in the Hospital "St. Marina" - Varna. The determination of the population includes preinspection of the register of General TEMC at University Hospital "St. Marina" - Varna and the Regional Card-index of Medical Expertise (RCME), Varna and covers 6000 patients with disability. A representative sample was formed on the basis of selection criteria and included 612 PD subject to certification and re-certification of General Territory Expert Medical Commission at University Hospital "St. Marina" - Varna for the period March-April 2018, which represents 10.25% of the population. Amongst the methods of the survey is a questionnaire, consisting of 15 questions in total (13 multiple-choice questions and 2 free-answer questions. The questions are organized in five domains: "organizational-methodical" (questions 2,6 and 7), "social" (questions 3, 5, 8, 9 and 11), "medical" (questions 1 and 4), "juridical" (questions 10, 12 and 13) and "opportunities for change" (questions 14 and 15). Standardized α-Crownbach 0.65. Results: Only 4.4% (n=612) of the people with disability, determined by TEMC-decision, think that rehabilitation that aims to restore their ability to work is enough. Those of them (81.9% (n=209)) who've been deprived of their percent for Permanently Diminished Working Capacity, report that they are not following the route of rehabilitation. The patients give different offers: a work recommendation must be included in the TEMC-decision (the type of labour must be synchronized with the given disability); the committee must influence the clinical and social rehabilitation that aims the restoration of temporary or permanent disability. Conclusions: The TEMC-decision does not help with the achievement of a prophylactic and rehabilitation function of the TEMC nor the restoration of the ability to work. There must be put an emphasis on a few subjects during the reforming process of the TEMC-system, such as the activities regarding the restoration of work capacity, a prequalification according to the disability and a work recommendation.